(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article is devoted to legal and ethical problems pertaining to the use of artificial intelligence (hereinafter – AI) in law. AI solutions are already being applied in some areas of law, and the use of AI will undoubtedly be expanding. There are problems relating to the regulatory framework because AI has no expressly defined legal status and the scope of AI is not clear either. AI could successfully be employed for data processing in certain areas, such as forensic science and criminology, as well as legal proceedings, where AI could assess procedural documents for their conformity with formal requirements, namely as a means of assisting a human, who is a decision maker. Recognising AI’s decision-making ability is extremely challenging. Thus, AI would transform from a means into a subject of law empowered to make decisions about other subjects of law. The existing legislation is not ready to embrace it, and AI’s decision-making ability is related to issues of an ethical nature, considering that decisions about people would be made by a non-human subject.